Implementation of Dry Hydrated Potassium Carbonate Carbon Capture - Jacobson, Kajsa; Törnqvist, Frida (My University, 2024)
In near future, Waste-to-Energy (WtE) plants are required to reduce their CO2 emissions drastically in order to achieve carbon neutrality. Since energy recovery from waste likely will persist, a necessary mitigation strategy is to implement a Carbon Capture and Storage (CCS) technology on site. In contrast to conventional methods, Dry Hydrated Potassium Carbonate (DHPC) carbon capture can provide low energy penalty, easy regeneration and opportunities to integrate the excess heat in the District Heating (DH) system. The DHPC process is based on solid absorp tion and performed by circulating a sorbent, potassium carbonate, K2CO3, between two fluidized bed reactors. This thesis performs a case study which implements the DHPC process at Renova’s WtE plant in Sävenäs. The application of the DHPC carbon capture is investigated by modeling the WtE and the DHPC process, using the simulation tools Ebsilon and Aspen Plus, re spectively. When modeling the capture process according to the design proposed in research, an alternative design of the regeneration reactor is discovered able to reduce its steam demand, the fluidized bed heat exchanger (FBHE). The FBHE configuration as well as the original design of the DHPC process, lay the foundation for the construction of multiple system cases to analyse throughout the project. The potential for heat integration, in the different cases, is evaluated by performing a pinch analysis which creates the basis for retrofitting the WtE plant. In addition, the energy performance, reactor sizes and capture cost are investigated. The thesis reveals that the DHPC process is a promising CCS method for Renova, especially the case using a FBHE. In particular, integrating this capture process increases the delivery of DH by 2.27-3.29% while reducing the electricity production by 2.09-8.51%, depending on the pressure level of the utilized steam. As a result, the total energy efficiency of the WtE plant is expected to increase by 1.47-1.57%, after applying the FBHE DHPC processes. In addition, the economic evaluation indicates on low capture costs including operational costs which are relatively in sensitive in terms of future energy prices. In conclusion, it is recommended for Renova to investigate the DHPC process fur ther, since by choosing this method, the WtE plant can almost maintain its normal production of electricity and DH. However, in order to enable a future implementa tion of the process, it is of importance to verify the function of the FBHE reactor and evaluate the physical footprint of the system in the light of the found reactor sizes as well as the practical feasibility of the proposed retrofits.
Keywords: CCS; WtE; DHPC; Process Modeling; Heat Integration; Pinch analysis; FBHE